2021
DOI: 10.22434/ifamr2020.0188
|View full text |Cite
|
Sign up to set email alerts
|

Post-acquisition integration and growth of farms: the case of Ukrainian agroholdings

Abstract: This paper presents a dynamic perspective on the processes of farm restructuring following farm acquisitions by large-scale agroholdings in Ukraine. In particular, the paper employs a large dataset of farm-level data and several quantitative techniques to explore how the acquired farms’ resource bases are integrated after acquisitions and what outcomes an acquisition brings about for farm growth, profitability and productivity. In general, acquisitions positively affect farm growth and productivity while agroh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The largest agroholdings in terms of land area, such as Kernel and Ukrlandfarming, operate about 500,000 hectares of farmland each (Latifundist.com, 2020). Furthermore, agroholdings account for approximately one fifth of total crop production and one third of total livestock production in Ukraine today (Ostapchuk et al, 2021a).…”
Section: International Food and Agribusiness Management Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest agroholdings in terms of land area, such as Kernel and Ukrlandfarming, operate about 500,000 hectares of farmland each (Latifundist.com, 2020). Furthermore, agroholdings account for approximately one fifth of total crop production and one third of total livestock production in Ukraine today (Ostapchuk et al, 2021a).…”
Section: International Food and Agribusiness Management Reviewmentioning
confidence: 99%
“…Especially, publicly listed agroholdings in Ukraine have been found to deploy instruments such as diverse executive boards, independent auditing and disclosure of information on ownership and financial aspects, which altogether function as protective mechanisms against obscure operational practices commonly encountered in transitional economies . As regards the cumulativeness effect, Ostapchuk et al (2021a) have shown how Ukrainian agroholdings make use of more open and competitive markets not only via acquiring less competitive farms but also by making these farms more efficient through complex resource reconfiguration processes.…”
Section: International Food and Agribusiness Management Reviewmentioning
confidence: 99%
“…Meanwhile, following Sisman et al (2023), real estate valuation constitutes an objective field of study based on scientific foundations that should consider social justice. Ostapchuk et al (2021) point out that there are several factors the value of land resources depends on, related to the market value of properties or the sustainable value defied by Walacik et al (2020). The factors include, among others: land allocation, zoning, land use planning, infrastructure development, relationship between demand and supply on the given market, environmental regulations, the properties of soils, its productivity, the valueadded premium, the surrounding area, inflation, benchmark land prices.…”
Section: Introductionmentioning
confidence: 99%
“…These developments have raised concerns that family‐based farming, in particular, may be affected negatively (Ciaian & Swinnen, 2006; Curtiss et al, 2020; Langenberg & Theuvsen, 2016). Though many of the large farms and enterprises in central and eastern Europe inherited their size from predecessors under socialism or through mergers and acquisitions (Ostapchuk et al, 2021a, 2021b), Graubner et al (2021) found evidence for Ukraine that large agroholdings may exercise local land‐market power by paying higher land prices and thus deterring entry for smaller farms.…”
Section: Introductionmentioning
confidence: 99%
“…inherited their size from predecessors under socialism or through mergers and acquisitions (Ostapchuk et al, 2021a(Ostapchuk et al, , 2021b, Graubner et al (2021) found evidence for Ukraine that large agroholdings may exercise local land-market power by paying higher land prices and thus deterring entry for smaller farms.…”
mentioning
confidence: 99%